Understanding of Low‐Porosity Sulfur Electrode for High‐Energy Lithium–Sulfur Batteries - Fu, Yucheng; Singh, Rajesh K; Feng, Shuo; Liu, Jun; Xiao, Jie; Bao, Jie; Xu, Zhijie; Lu, Dongping (Advanced energy materials, 2023)
The lithium–sulfur (Li–S) battery is a promising technology for large‐scale energy storage and vehicle electrification due to its high theoretical energy density and low cost. Reducing the sulfur cathode porosity has been identified recently as a viable strategy for improving the cell practical energy density and minimizing pore‐filling electrolytes to extend cell life at lean electrolyte conditions. Direct use of a low‐porosity cathode for Li–S battery results in poor electrode wetting, nonuniform electrode reactions, and thus early cell failure. To understand and mitigate the barriers associated with the use of low‐porosity electrodes, multiscale modeling is performed to predict electrode wetting, electrolyte diffusion, and their impacts on sulfur reactions in Li–S cells by explicitly considering the electrode wettability impacts and electrode morphologies. The study elucidates the critical impact of low tortuosity and large channel pore design for promoting electrode wetting and species diffusion. It is suggested that the secondary particle size should be comparable with the electrode thickness to effectively promote electrolyte wettability and sulfur reactivity. This study provides new insights into the low‐porosity electrode material and designs and is expected to accelerate the development of practical high‐energy Li–S batteries. Multiscale modeling and experimental approaches are used to study the working principle of the low‐porosity cathode for lithium–sulfur batteries. Increasing cathode secondary particle size and reducing pore channel tortuosity can promote electrolyte wettability and sulfur reactivity, which makes reducing cathode porosity a viable strategy for improving the cell practical energy density and cycling life at lean electrolyte conditions.